2001
DOI: 10.1016/s0304-3959(00)00370-5
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor regulates VR-1 mRNA levels in cultures of adult dorsal root ganglion neurons

Abstract: Nerve growth factor (NGF) regulates the nociceptive properties including sensitivity to capsaicin of a subset of dorsal root ganglion neurons, which express the high-affinity NGF receptor, trkA. Capsaicin sensitivity co-localizes with the expression of a cloned capsaicin receptor, vanilloid receptor type 1 (VR-1), which displays properties similar to the native capsaicin response. To determine whether VR-1 mRNA levels are regulated by NGF, VR-1 mRNA levels and the ability to respond to capsaicin by release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 28 publications
11
101
2
Order By: Relevance
“…The present study showed the upregulation in TRPV1 mRNA/protein in the uninjured DRG, although several studies have demonstrated an increase in the TRPV1 protein but not in its mRNA, after peripheral inflammation (Tohda et al, 2001;Ji et al, 2002). The reasons for this discrepancy are not clear, but other reports have shown that inflammation and/or NGF increased TRPV1 mRNA in adult DRG neurons (Winston et al, 2001;Amaya et al, 2003).…”
Section: Bdnf and Trpv1 Expression In Adjacent Intact L4 Drg Neurons contrasting
confidence: 79%
See 1 more Smart Citation
“…The present study showed the upregulation in TRPV1 mRNA/protein in the uninjured DRG, although several studies have demonstrated an increase in the TRPV1 protein but not in its mRNA, after peripheral inflammation (Tohda et al, 2001;Ji et al, 2002). The reasons for this discrepancy are not clear, but other reports have shown that inflammation and/or NGF increased TRPV1 mRNA in adult DRG neurons (Winston et al, 2001;Amaya et al, 2003).…”
Section: Bdnf and Trpv1 Expression In Adjacent Intact L4 Drg Neurons contrasting
confidence: 79%
“…Seven days after surgery, both BDNF and TRPV1 were detected in ϳ80% of p-p38-labeled neurons. NGF, p38 activation, and BDNF and TRPV1 expression in the uninjured L4 DRG NGF injection in a peripheral target induces p38 activation in small DRG neurons (Ji et al, 2002;Delcroix et al, 2003), and NGF also increases the production of BDNF and TRPV1 mRNA through trkA receptors (Apfel et al, 1996;Winston et al, 2001). To elucidate whether alterations in endogenous NGF can trigger changes in L5 SNL-induced thermal hyperalgesia, activation of p38, and, furthermore, upregulation of BDNF and TRPV1 in the ipsilateral L4 DRG, we administered anti-NGF into the intrathecal space via a catheter, the tip of which was positioned close to the L4/5 DRG.…”
Section: Figure 6 Effects Of L4 or L5 Dorsal Rhizotomy (Dr) On L5 Snmentioning
confidence: 99%
“…The interaction of NGF with the TrkA receptor represents a key event in the activation and sensitization of primary afferents nociceptors and in following central changes. The NGF/ TrkA system is a sort of master control system in the spreading of inflammation around the nociceptive terminal, because it is functionally placed upstream of many different molecular partners involved in inflammation (including the NGF/TrkA system itself), and it regulates the expression and function of ion channels conveying nociceptive signals (C-fiber nociceptors), including the transient receptor potential vanilloid receptor 1 (TRPV1) (38,39), the P2ϫ3 ATP receptors (40), and the tetrodotoxin (TTX)-resistant SNS sodium channel (41). TRPV1 undergoes sensitization 10; 3.75 g, n ϭ 9; 7.5 g, n ϭ 9; 15 g, n ϭ 10; 30 g, n ϭ 10; 60 g per mouse, n ϭ 9).…”
Section: Discussionmentioning
confidence: 99%
“…Reflex (sneeze) and local (plasma protein extravasation) responses to the vanilloid receptor agonist capsaicin are enhanced in human subjects with rhinitis (33). Nerve growth factor (NGF) expression is enhanced in allergic airway inflammation (10,33), and NGF has been shown to influence vanilloid receptor expression (19,23,47).…”
Section: Discussionmentioning
confidence: 99%